Determinação de diâmetros médios em micrometria. I - obtenção da ortogonalidade entre o maior e o menor diâmetro, através de ocular micrométrica simples - Piza, Ivan Giacomo (Semina: Ciências Agrárias, 1984)
Orthogonality between major and minor measuring diameters is an essential requirement when mean diameter determination has to be performed. For the microscopic dimensions, however, simple micrometer eyepieces and its conventional usage don't provide that geometric relation. In order to attend to that requirement, a new procedure for the use of such a file is presented.